Medical cyclotron: Operational aspects and its clinical utility - Rajeev Kumar; Arunav Kumar; Santosh Kumar; Sanjay Kumar Suman; Nihar R. Biswas (Wolters Kluwer -Medknow Publications, 2022)
Cyclotron is a type of particle accelerator invented by Ernest O. Lawrence in 1930 at the University of California, Berkeley and patented in 1932. Lawrence was awarded the Nobel Prize in Physics 1939 for this invention. It is based on a combination of radiofrequency acceleration and bending of charged particles in a magnetic field. This way the same electrode is used over and over again to give acceleration to the particles. Lawrence built the first cyclotron in 1931 and it produced Protons of 1.25 MeV. In a conventional Cyclotron, the charged particles move in two semicircular metal containers called Dees (because of the D-shaped electrodes). In most of the modern medical cyclotrons, there are four gaps with four pie-shaped Dees instead of two. The particles pass through the same acceleration gap many times with increasing radius before they acquire the desired energy. The entire accelerating system is maintained at high vacuum (10-6 to 10-8 Torr), and the Dees are housed in a vacuum chamber. Hydrogen gas is passed through an arc current to produce the ion source for the acceleration in the cyclotron. The ion source is pulled toward the center of Dee structure by applying a positive bias voltage. A high voltage (>36 kV) is applied to the Dee structure with the help of an oscillator. The ion located at the center is thus attracted toward a Dee that happens to be at the opposite potential at that particular moment. As the magnetic and electric fields (in Dees) in the cyclotron are at right angles to each other the ion beam moves in a circular path inside the hollow Dees. In the present scenario, negative ion cyclotron accepted everywhere in the medical field. The objective of this article is to educate the new generation of physicians and share the knowledge of medical cyclotron and its integrity mainly among our colleague apart from nuclear medicine. Hence, that they can understand about this complex and complicated equipment and its medical utility for patients benefit.